Karakteristik dan Sifat-Sifat Dasar Kayu Jati Unggul Umur 4 dan 5 Tahun Asal Jawa Barat - Imam Wahyudi; Trisna Priadi; Istie Sekartining Rahayu (Institut Pertanian Bogor, 2014)
Anatomical characteristics, fiber morphology, microfibril angle, specific gravity and wood density, dimensional stabilization, modulus of rupture (MOR), modulus of elasticity (MOE), hardness and natural durability of superior teakwood from West Java were studied comprehensively in order to find out their best quality improvement technique. It was showed that quality improvement technique has to be employed since characteristics and properties of the superior teakwood studied are inferior compared to those of the older teakwood. In general wood strength, wood durability, wood stability and wood figure were lower compared to those of the conventional teakwood.